HUBUNGAN INTENSITAS MEMBACA DENGAN KEMAMPUAN MENULIS KARANGAN SISWA KELAS V SEKOLAH DASAR - Tania Erika Saputri; Adjeng Diahmart Venta; Siti Sopiani; Darwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school students' essay-writing ability is often hindered by low reading intensity, in terms of frequency, duration, and the variety of reading materials accessed. This study aims to map the relationship between reading intensity and essay-writing ability among fifth-grade elementary students, identify the most frequently studied indicators, and formulate pedagogical implications for teachers. A Systematic Literature Review approach following the PRISMA protocol was applied, with article searches conducted on Google Scholar and Garuda for the 2018–2026 period, limited to Indonesian-language publications. Through four selection stages, 20 final articles were obtained and analyzed using descriptive thematic analysis. The results show a positive and significant relationship between reading intensity and essay-writing ability, covering narrative, descriptive, and poetic essays, with correlation strength ranging from moderate to very high. Reading habituation and parental support were the main supporting factors, while auditory learning styles and digital distractions were the main inhibiting factors. It is concluded that increasing reading intensity is a fundamental strategy for improving elementary students' essay-writing ability.